Access to Behavioral Health Care Services in New Jersey. Issue 3 (3rd July 2017) - Holstein, Russell M.; Paul, David P.
ABSTRACT: Patients with health insurance may find that obtaining an initial appointment for behavioral healthcare is an arduous process. A stratified sample of licensed New Jersey psychiatrists and psychologists was surveyed by telephone. Results revealed that patient access to care under 10 large insurance plans in New Jersey varies by plan, but overall was difficult. Suggestions for dealing with the problem are offered. Behavioral health practitioners and their professional organizations should address these issues more directly and vigorously.